Clinical features and gene variation analysis of COQ8B nephropathy: Report of seven cases - Rui Liang; Xuelan Chen; Ying Zhang; Chak-Fun Law; Sijie Yu; Jia Jiao; Qin Yang; Daoqi Wu; Gaofu Zhang; Han Chen; Mo Wang; Haiping Yang; et al. (Frontiers Media S.A., 2023)
ObjectiveCOQ8B nephropathy is a relatively rare autosomal recessive kidney disease characterized by proteinuria and a progressive deterioration of renal function, eventually leading to end-stage renal disease (ESRD). The objective is to study the characteristics and correlation between the genotype and the clinical phenotype of COQ8B nephropathy.MethodsThis is a retrospective study focusing on the clinical characteristics of seven COQ8B nephropathy patients diagnosed by gene sequencing. Basic clinical information, clinical manifestations, examinations, imaging, genomes, pathology, treatments, and prognosis of the patients were reviewed.ResultsOf the seven patients, two were male children and five were female children. The median age at the disease onset was 5 years and 3 months. The initial main clinical manifestations were proteinuria and renal insufficiency. Four patients had severe proteinuria, four had focal segmental glomerulosclerosis (FSGS) diagnosed by a renal biopsy, and two had nephrocalcinosis after an ultrasound was performed on them. There were no other clinical manifestations such as neuropathy, muscle atrophy, and so on in all of them. Their gene mutations were all exon variants, which were classified as heterozygous or homozygous variants by performing family verification analysis. Compound heterozygous variants were predominant in all, and all gene variants were inherited from their parents. One novel mutation, c.1465c>t, was found in this study. This gene mutation resulted from changes in the amino acid sequence, thus leading to an abnormal protein structure. Two patients with early diagnosis of COQ8B nephropathy presented with no renal insufficiency and were treated with oral coenzyme Q10 (CoQ10), and they maintained normal renal function. For the remaining five who were treated with CoQ10 following renal insufficiency, the deterioration of renal function could not be reversed, and they progressed to ESRD within a short time (median time: 7 months). A follow-up of these patients showed normal renal function with a CoQ10 supplement.ConclusionFor unexplained proteinuria, renal insufficiency, or steroid-resistant nephrotic syndrome, gene sequencing should be considered, in addition to renal biopsy, as early as possible. Timely diagnosis of COQ8B nephropathy and early supplementation of sufficient CoQ10 can help control the progression of the disease and significantly improve the prognosis.